Analysis of the scientific production on crisis management in tourism during the period 1980-2021 - Ramos-Giral, Glessler Vladimir; Batista-Matamoros, Carlos Rafael; Torralbas-Blazquez, Ana de Lourdes (Bibliotecas. Anales de investigación, 2022)
Objective. Analyze the scientific production on crisis management in tourism in the Scopus database in the period 1980-2021. Design/Methodology/Approach. A bibliometric study was carried out in the Scopus database using the keyword search strategy with the terms “crisis management” AND “tourism”. Results/Discussion. The search yielded a total of 395 articles indexed in the database; 76.46% (302) of them are articles from scientific journals, the largest number of publications are associated with the Tourism Management journal and Lori Pennington-Gray stands out as the most prolific author on the subject. A total of 1045 keywords were analyzed through the co-occurrence of terms with prevalence of studies associated with crisis management related to tourism management, tourism economies, market studies, tourism destinations, tourism development, COVID-19, social networks, decision making, among others. Conclusions. Crisis management is a topic of growing interest within the international scientific community, which is proven by the increase in publications associated with it, especially during the crisis caused by COVID-19 in the tourism sector the last two years. Originality / Value. This research is part of a larger research project focused on the development of a doctoral thesis associated with the subject under study.